Democracy and difference : contesting the boundaries of the political - Benhabib, Seyla (Princeton University Press, 1996)
The global trend toward democratization of the last two decades has been accompanied by the resurgence of various politics of "identity/difference." From nationalist and ethnic revivals in the countries of east and central Europe to the former Soviet Union, to the politics of cultural separatism in Canada, and to social movement politics in liberal western-democracies, the negotiation of identity/difference has become a challenge to democracies everywhere. This volume brings together a group of distinguished thinkers who rearticulate and reconsider the foundations of democratic theory and practice in the light of the politics of identity/difference
Keywords: Democracy.; Ethnicity.; Nationalism.; Social movements.; Nationalism; Democracy; Démocratie.; Ethnicité.; Nationalisme.; Mouvements sociaux.; ethnicity.; nationalism.; social movements.; democracy.; 89.06 political philosophy.; 89.35 democracy.; 08.45 political philosophy.; POLITICAL SCIENCE -- History & Theory.; Ethnicity; Social movements; Demokratie; Nationalbewusstsein; Nationalismus; Kulturelle Identität; Aufsatzsammlung; Ethnizität; Democratie.; Nationale identiteit.; Culturele identiteit.; Democracia (teoria); Democracia (modelos); Democracia (cultura); Cidadania.; Multiculturalismo.; Representação política.; Identidade cultural.; Aufsatzsammlung.